BODY DIMENSIONS OF FINISHER PHASE LANDRACE FED BY CONCENTRATED FEED WASTE OF BROILER HUSBANDRY CLOSED HOUSE SYSTEM - G. G. K., Bayu; Ariana, I N. T.; Sriyani, N. L. P. (Jurnal Peternakan Tropika; Vol 12 No 2 (2024): Vol. 12 No. 2 Tahun 2024; March - April, 2024)
Research on aims to determine the body dimensions of pigsland racefed concentrate broiler farm waste (KPLB) in the systemclosed house through pork rations. The research was carried out from March 20 2022 to June 5 2022 in the pig pen of the Bukit Jimbaran Research Station/Farm, Faculty of Animal Husbandry, Udayana University. The design used in this study was a completely randomized design (CRD) with three treatments and each treatment was repeated four times. The three treatments consisted of A: Rations with no KPLB/Control, B: Rations with 12% KPLB, and C: Rations with 24% KPLB. Variables observed in this study were body weight gain (PBB), body length, body height, chest circumference, and hip width of pigs. The results of this study indicated that substituting commercial rations with KPLB had a significantly different effect (P<0.05) on body length and hip width, whereas for UN, body height and chest circumference were not significantly different (P>0.05). The results of the study concluded that substitution of commercial rations with KPLB at the level of 12% and 24% resulted in body weight gain, height, and chest circumference, resulting in the same weight for each treatment. Substitution of the commercial ration with KPLB at a level of 24% resulted in the lowest body length and hip width of the other treatments.